Recent achievements in the synthesis and reactivity of pentafluorosulfanyl-alkynes - René, Floriane; Clément–Comoy, Léo; Blanchard, Nicolas; Bizet, Vincent (Comptes Rendus. Chimie)
In the dynamic field of pentafluorosulfanyl (SF5) chemistry, the SF5-alkynes have emerged as essential, readily accessible, and modular building blocks for the construction of a wide variety of SF5-containing molecules. This polarized platform has been used to perform highly regio-, chemo-, and stereoselective transformations such as heterocycle synthesis, cycloaddition, and hydroelementation reactions. This brief review provides an overview of recent developments in the synthesis and reactivity of SF5-alkynes, which are fascinating building blocks that have yet to reveal their full synthetic potential.